Gold nano-urchins enhanced surface plasmon resonance (SPR) biosensors for the detection of estrogen receptor alpha (ERα) - Pae, Jian Yi (2021)
Breast cancer is the deadliest form of cancer in women, but it also has very high survival rates when treated early. Existing breast cancer detection methods such as mammography are ineffective in the early detection of breast cancer due to the low uptake among women and the need for regular screening. Therefore, biosensors have been proposed as an alternative method for cost-effective breast cancer screening which may encourage more women to go for screening more regularly. In this paper, a gold nano-urchins enhanced plasmonic sensor is demonstrated for the detection of a typical breast cancer marker, estrogen receptor alpha (ER). The localized field confinement effect due to the sharp features of the nano-urchins amplifies the biosensing signal and improves its sensitivity as compared to a conventional surface plasmon resonance (SPR) biosensor.